2003
DOI: 10.1007/s10147-003-0354-4
|View full text |Cite
|
Sign up to set email alerts
|

Eradication and reinfection of human papillomavirus after photodynamic therapy for cervical intraepithelial neoplasia

Abstract: PDT is effective not only in improving the cytological and histological measures when treating CIN but also for eradicating cervical HPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 11 publications
0
17
0
2
Order By: Relevance
“…They occur on the male or female external genitalia, around the anus, and in women HPV infects the uterine cervix where (if the virus is type 16 or 17) it can lead to development of cervical intraepithelial neoplasia (CIN) and cervical cancer. Ichimura et al showed PDT (with a 630-nm YAG-OPO laser after 60 h of polyhematoporphyrin ether/ester 2 mg/kg IV) was effective not only in improving the cytological and histological measures when treating CIN but also for eradicating cervical HPV (115). …”
Section: Pdt For Clinical Infectious Diseasementioning
confidence: 99%
“…They occur on the male or female external genitalia, around the anus, and in women HPV infects the uterine cervix where (if the virus is type 16 or 17) it can lead to development of cervical intraepithelial neoplasia (CIN) and cervical cancer. Ichimura et al showed PDT (with a 630-nm YAG-OPO laser after 60 h of polyhematoporphyrin ether/ester 2 mg/kg IV) was effective not only in improving the cytological and histological measures when treating CIN but also for eradicating cervical HPV (115). …”
Section: Pdt For Clinical Infectious Diseasementioning
confidence: 99%
“…In this study we expand on our preliminary report of the therapeutic effect of PDT in 31 CIN cases which suggested that PDT is effective for treating cervical dysplasia, and for the eradication of cervical HPV [12]. We now describe the effectiveness PDT in 105 cases, of CIN with a median follow-up period of 636 days.…”
Section: Introductionmentioning
confidence: 99%
“…Ces derniers entraînant la lyse cellulaire. Plusieurs études ont démontré l'avantage de la thérapie photodynamique (PDT) dans le traitement des SIL réduisant le risque de saignement après conisation, et améliorant les résultats à long terme diminuant les sténoses cervicales et les menaces d'accouchement prématuré [22,[25][26][27][28][29][30]. Les techniques de PDD et de PDT sont prometteuses mais toujours en cours d'expérimentation en gynécologie.…”
Section: Discussionunclassified